Tinjauan Hukum terhadap Mekanisme Gugatan Sederhana di Pengadilan Agama: Perspektif Asas Sederhana, Cepat, dan Biaya Ringan - Mu'ala, Abdulloh Afifil (Taruna Law: Journal of Law and Syariah, 2025)
This study aims to analyze the implementation of the small claims mechanism in Religious Courts based on the principles of simplicity, speed, and low cost. This study uses a normative juridical method by reviewing laws and regulations such as PERMA Number 2 of 2015 in conjunction with PERMA Number 4 of 2019, as well as relevant legal literature. The results of the study indicate that small claims in Indonesia are an innovation of the small claims court concept in various countries and are regulated in PERMA Number 2 of 2015 in conjunction with PERMA Number 4 of 2019. Its application to Islamic economic cases in Religious Courts is a concrete manifestation of the implementation of the principles of simple, fast, and low cost justice as stated in Article 2 paragraph (4) of Law Number 48 of 2009 concerning Judicial Power. The appointment of a single judge in small claims also speeds up the trial process and reduces formalities, thereby providing wider access to justice. This study concludes that small claims are an important breakthrough in the modernization of the civil justice system in Indonesia, especially in the realm of Religious Courts because they reflect the principles of simplicity, speed, and low cost.